Evaluate the Efficiency of Some Retrofit Measures in One of Local Bridge Models Based On Seismic Fragility Curves (Case Study of Al Rimal Bridge on Lattakia -Tartous Road) - نايل حسن; بسام حويجة; حنان حسين (Latakia University Journal -Engineering Sciences Series, 2023)
In view of the great development of seismic design requirements for bridges, and their association with the required performance, there is a need to evaluate the performance of the existing bridges to verify their ability to withstand possible earthquakes and their need for rehabilitation. Probabilistic evaluation is one of the latest methods because it takes into account the unreliability of both demand and capability, and predicts the level of damage for a large range of seismic intensities; also it can be a useful tool for comparing the available retrofit options. In this paper, we developed the seismic fragility curves for Al Rimal Bridge on the Syrian coast (as it is structurally similar to a large number of local bridges), that was for the current state of the bridge and also for some of the retrofitting options proposed based on its expected behavior to determine their effect in improving its performance. The bridge was modeled using csibridge v20, and nonlinear static analysis was performed. Different damage states were identified for both columns and bearings, and the expected damage level was determined for 50 different seismic spectra, and then we compared the resulting curves. As a result we found that this model of bridges suffers a weakness in the bearings, also the results showed that the impact of the retrofitting measures on the vulnerability differs from one damage state to another, and that the local strengthening of a component can adversely affect the overall performance of the bridge and increase the likelihood of damage.